Real Risk-Free Rate, the Central Bank, and Stock Market Bubbles - Ilomäki, Jukka; Laurila, Hannu (Journal of Reviews on Global Economics, 2017)
The central bank acts as a social planner, and adjusts the real risk-free rate of return to correct any mispricing in the stock market so that the emergence of positive or negative bubbles is avoided. The analysis shows that the central bank must raise the risk-free rate in the case of a positive bubble, and vice versa. Moreover, the central bank should intervene in the stock market even if it does not have perfect information about the bubble. This is because the sequential dividend yields in the pricing equations are stationary. Thus, even the delayed reaction of the central bank prevents the fundamental value and the equilibrium price from drifting apart for extended periods.